Perception of family members of children with Autism Spectrum Disorder (ASD) about the role of nursing: A report of experience (Research, Society and Development, 2024)
This article aims to describe the perception of family members of children with ASD regarding the role of nursing in the care and support provided, highlighting the impact of this support on the families’ quality of life and the child’s social integration. It is a descriptive study with a qualitative approach, based on an experience report, conducted at the TEAceito association in the interior of Bahia, Brazil, through discussion groups led by family members of children with ASD, between May 5 and 6, 2024. The objective was to describe the perception of family members of children with Autism Spectrum Disorder (ASD) regarding the role of nursing in the care and support of these children. The results showed that the discussion groups facilitated the sharing of knowledge and experiences among participants, emphasizing the importance of nursing in early diagnosis, guidance, and continuous support to families. It is concluded that the active involvement of nursing professionals is crucial for improving the quality of life of children with ASD and their families, providing guidance, emotional support, and training to deal with the specific challenges of the disorder.